Attention Problems as a Predictor of Type 1 Diabetes Adherence and Metabolic Control Across Adolescence. (13th May 2017) - Turner, Sara L; Berg, Cynthia A; Butner, Jonathan E; Wiebe, Deborah J
Abstract: Objective: Management of type 1 diabetes is a difficult self-regulatory process requiring continued attention to complex regimen tasks. The purpose of this study was to examine whether youths' attention problems were associated with poorer adherence and HbA1c across time, and whether higher parental involvement reduced these associations. Methods: Adolescents with type 1 diabetes ( N = 199, M age = 12.43 years, SD = 1.50) and their mothers rated youths' attention problems and adherence at three time points. Adolescents rated parents' diabetes-specific monitoring and behavioral involvement. HbA1c was collected from medical records. Results: Adolescents' (but not mothers') greater reports of attention problems compared with their average related to lower adherence across time. Adolescents' (but not mothers') reports of greater attention problems compared with their average related to lower adherence across time. Conclusions: Youth attention problems may help us understand poor adherence, and interventions to promote parental involvement may buffer this risk.